ChemInform Abstract: Ruthenium(II) Catalyzed Synthesis of Unsaturated Oxazolines via Arene C—H Bond Alkenylation. Issue 6 (20th February 2013) - Li, Bin; Devaraj, Karthik; Darcel, Christophe; Dixneuf, Pierre H.
Abstract Monoalkylation of arene C—H bonds directed by an oxazoline group to afford bifunctional alkenes (III) is reported.